Sự phối hợp giữa nhà trường và ngành công nghiệp trong giáo dục dạy nghề - một số kinh nghiệm từ Indonesia, Hàn Quốc và Nhật Bản - Trần Vũ Quỳnh Như (Journal of Technical Education Science, 2006)
The Vietnamese young workforce, from 15 to 24 years old, is about 20% of the population. This is one of the advantages of the national economy. However, the trained-labors are about 24,8% in total (source from Ministry of Labor, War Invalids and Social Welfare, 2005). Moreover, the quality even does not meet the requirements of the labor market. Meanwhile, the demand of skilled labors, especially from important industrial areas such as HCM City, Dong Nai, Binh Duong, etc…, increases rapidly. The question is how to solve this workforce problem? This report aims to introduce the experiences from Indonesia, Korea and Japan in Technical and Vocational Education reform.